2019
DOI: 10.1111/asj.13228
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary supplementation with porous zinc oxide on growth performance, intestinal microbiota, morphology, and permeability in weaned piglets

Abstract: The objective of this experiment was to evaluate the effects of dietary supplementation with porous zinc oxide (HiZox) on growth performance, intestinal microbiota, morphology, and permeability in weaned piglets. A total of 128 weaned piglets [(Landrace × Yorkshire) × Duroc] with an average body weight (BW) of (6.55 ± 0.25 kg; 21 d of age) were randomly assigned to four dietary treatments: (1) a corn‐soybean basal diet; (2) basal diet + 3,000 mg/kg conventional ZnO; (3) basal diet + 200 mg/kg HiZox; (4) basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Zinc administration influences the development of the intestinal tissue structure and immune system. Many studies have reported that the administration of zinc oxide for over three weeks changes intestinal morphology [ 13 , 56 , 57 ]. Some studies also reported that after a two-week experiment, the morphology of the jejunum differs between piglets treated with a high dose of ZnO (2000–2250 ppm) compared to those in the negative control or treated with a low dose of different types of zinc oxide [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc administration influences the development of the intestinal tissue structure and immune system. Many studies have reported that the administration of zinc oxide for over three weeks changes intestinal morphology [ 13 , 56 , 57 ]. Some studies also reported that after a two-week experiment, the morphology of the jejunum differs between piglets treated with a high dose of ZnO (2000–2250 ppm) compared to those in the negative control or treated with a low dose of different types of zinc oxide [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal tract is not only the place where nutrients are digested and absorbed [ 63 ] but also a site of immune defense, an important barrier against exogenous pathogens [ 64 ]. D-Lac and ET are the products secreted by the inherent bacteria of the gastrointestinal tract, and increases in their concentrations in the blood reflect the dysregulation of the intestinal flora and impaired permeability [ 65 , 66 , 67 , 68 ]. In this study, the intestinal D-Lac and ET contents increased in the diets SBM60 vs. that in the diets FM.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning and end of the experiment, all piglets were weighed individually, and residual feed was collected and weighed for each pen; ADG, ADFI, and FCR were calculated. Occurrences of diarrhea were recorded every day at 09:00 using the scoring system described by Yang et al [ 15 ]. The scoring system was applied to determine the rate of diarrhea as follows: 0 = hard feces; 1 = slightly soft feces; 2 = soft, partially formed feces; 3 = loose, semiliquid feces; 4 = watery, mucous-like feces.…”
Section: Methodsmentioning
confidence: 99%